Are Neonatal Birth Weights Reduced in Low-Risk Patients Diagnosed with COVID-19 during Pregnancy? - Foster, Hannah S.; Forkpa, Markolline; Van Tienhoven, Ximena A.; Schwartz, Nadav; Srinivas, Sindhu; Parry, Samuel; Mccabe, Meaghan G. (American Journal of Perinatology, 2024)
Objective Studies have shown that the 2019 novel coronavirus disease (COVID-19) may be associated with an increased risk of adverse pregnancy outcomes including preeclampsia, preterm birth, and stillbirth. However, the relationship between COVID-19 and abnormal fetal growth (i.e., low neonatal birth weight) has not been elucidated. Because other viruses affect fetal growth, obstetrical providers began to recommend ultrasound studies during the third trimester to assess fetal growth in patients with COVID-19 during pregnancy. The aim of this study was to determine if neonatal birth weight was different between low-risk patients diagnosed with COVID-19 during pregnancy and low-risk patients without COVID-19 in pregnancy, to ascertain if third trimester growth ultrasound is warranted in this patient population.Study Design We performed a retrospective cohort study of low-risk pregnant patients (who had no other indications for sonographic fetal surveillance during the third trimester) with and without COVID-19 during pregnancy. Patient demographics, gestational dating, neonatal birth weights, and corresponding Alexander growth curve birth weight percentiles were collected. The primary outcome was small-for-gestational age (SGA) neonates, defined as birth weight < 10th percentile for gestational age at delivery (SGA10).Results Our cohort (N = 513) included 248 COVID-19-exposed patients and 265 patients who did not have COVID-19 during pregnancy. Gestational age at delivery and average neonatal birth weights were similar in COVID-19-exposed (38 weeks 5 days, 3,266 g) and unexposed patients (38 weeks 4 days, 3,224 g; p = 0.434, 0.358). Rates of SGA10 neonates were similar in the COVID-19-exposed (22/248, 8.9%) and -unexposed (23/265, 8.7%, p = 0.939) groups. Timing and severity of COVID-19 during pregnancy also were not associated with rates of SGA neonates.Conclusion In a cohort of low-risk patients, rates of SGA neonates were similar in patients with and without COVID-19 during pregnancy. These findings suggest that ultrasound surveillance to detect fetal growth restriction in low-risk patients with COVID-19 during pregnancy is not warranted.Key Points
Keywords: COVID-19; fetal growth restriction; neonatal birth weight; pregnancy; ultrasound